LAND USE CHANGE REGARDING SPATIAL PLANNING IN MEDAN TUNTUNGAN DISTRICT - Indri Meiyanti; Abdi Sugiarto (PT. Radja Intercontinental Publishing, 2025)
Population growth, improving quality of life, and community welfare increase the need for land. The fixed amount of land triggers land use problems in rural and urban areas. Land use changes are significant in several areas in Indonesia, where these changes are often not in accordance with spatial plans. Spatial planning policies such as the Medan City RDTR Perda affect the dynamics of land use and require review along with changes in the strategic environment.The purpose of this study is to identify and analyze the types of land use that have developed in Medan Tuntungan District during the implementation period of the Medan City RDTR policy regulations andanalyze the suitability and non-suitability of land use to the Medan City RDTR zoning plan. This study is a descriptive-qualitative study using a geospatial analysis approach based on geographic information systems with overlay operations techniques in comparisons between spatial objects. The results of this study indicate that existing land use in 2015 in Medan Tuntungan District was dominated by non-built-up land covering an area of ​​2,077.07 hectares (72.38%) in most of the shrubs, fields, and plantations. Furthermore, in 2023 it was still dominated by non-built-up land covering an area of ​​1,770.93 hectares (61.71%), where in the eight-year period there was a significant change in land use covering an area of ​​695.23 hectares (23.23%). The dynamics of land use changes occurred in the conversion of non-built-up land to built-up land which decreased by -306.14 hectares (-10.67%), especially in rice fields (-110.75 hectares), fields (-134.68 hectares) and plantations (-77.78 hectares). The land changes were mostly converted into settlements, trade, and public service facilities, so it can be stated that there was a decrease in the function of productive agricultural land to built-up land in Medan Tuntungan District. In the suitability of land use in 2015 with the RDTR plan at the beginning of the RDTR planning year, it still had an implementation performance of 770.79 hectares or 26.86% as land use in accordance with the RDTR and had been realized. Then in 2023 there was an increase in implementation performance of 1,021.94 hectares or 35.61%. Meanwhile, the suitability of land use with the RDTR plan from changes in land use that occurred within eight years (2015-2023) includes 612.62 hectares (88.12%) that are in accordance with the RDTR directives and 82.60 hectares (11.88%) that are not in accordance with the RDTR directives. This shows that supervision of land conversion in protected areas, acceleration of the development of planned public service facilities, and re-evaluation of several zones that have not developed as expected are still needed.